Changes in the maritime sector over the years (impact on desirability of jobs) - Yeo, Jolinn Jin Wen (Nanyang Technological University, 2022)
The aim of this report is to provide the readers with a better understanding of the different changes in the shipping industry that has impacted their desirability of the various maritime jobs. The maritime industry and jobs at sea are almost as old as time itself. As the maritime industry evolves through the ages, the ways that ships evolve, their construction and technologies have changed too. Job requirements for seafarers have also changed, as today’s seaman can be seen developing his skills to deal and grapple with changes in his role. With everything changing from environmental regulations to cyber threats, today’s maritime industry has come a long way from its humble beginnings. With the increasing importance placed on digitalisation in the shipping industry, this report will also further look into the changes made to remain competitive.